A Structured Review and Critical Analysis of Male Perceptions of the Penis: A Comparison between Heterosexual Men and Men Who Have Sex with Men (MSM). (October 2019) - Simpson, Paul; Adams, Julie
Current research into male body image has identified several areas of body dissatisfaction among men, including perceptions associated with the penis. This is the first article to present a structured review, synthesis, and critical analysis of research into male perceptions of the penis, the psychosocial, and sexual correlates and to provide a comparison of outcomes between men who have sex with men (MSM) and heterosexual men. Analysis of twenty-six international studies suggests that men's accounts of the penis indicate diverse ways of negotiating normative masculinity. Key findings include that most men perceive their penis to be of an average size but would still like a larger one; and differences exist between MSM and heterosexual men in ratings of penis size, emphasis placed upon penis size, and impact of penis size upon sexual behavior. This narrative synthesis has addressed a gap in knowledge concerning how accounts of the penis by men expressing different forms of sexual identification indicate diverse ways of negotiating masculinity.